Effects of dietary chromium supplementation on dry matter intake and milk production and composition in lactating dairy cows: A meta-analysis - Malik, Muhammad I.; Raboisson, Didier; Zhang, Xin; Sun, Xuezhao (Frontiers in Veterinary Science, 2023)
Chromium (Cr) is an essential mineral and its supplementation in the diet can improve the milk production of dairy cows. The objectives of this study were to evaluate the effects of dietary Cr supplementation on dry matter intake (DMI) and milk production and composition using a meta-analysis based on existing literature. The DMI was increased by 0.72 kg/day [95% confidence interval (CI), 0.46 ˗ 0.97] in cows supplemented with Cr compared to those not supplemented. The heterogeneity of DMI was moderate (I2 = 54% and Q = 104.05). The regression model indicates that DMI significantly increased by 0.9 g/kg of body weight (BW) and by 80.5 g for an increase of 1 mg of Cr supplement. The supplementation phase [before (BFP) or after (AFP) parturition] was associated with an increase in DMI (0.4582 and 0.853 kg/day, respectively). The methionine and yeast forms of Cr increased DMI by 0.714 and 1.137 kg/day, respectively. The DMI were increased by 0.620 and 2.137 kg/day for multiparous (MP) and MP+ primiparous (PP) cows, respectively. Milk production increased by 1.20 kg/day (95% CI, 0.65-1.76) with Cr supplementation. The heterogeneity for milk production was moderate (I2 = 57% and Q = 100.03). Milk production was increased by 2.3 g/day for an increase of 1 kg of BW. Milk production also increased by 122.4 g/day with an increase of 1 mg of Cr. Milk production increased by 67.6 g/day for one expended week of the experiment duration. Similarly, milk production increased by 16.8 g/day for an extra day in days in milk. The amino acid and methionine forms of Cr complexes increased milk production by 1.645 and 1.448 kg/day respectively. The milk production increased by 1.087 and 1.920 kg/day for MP and PP cows respectively. The milk composition meta-analysis results revealed that the supplementation of Cr had no effect on milk protein, milk fat, milk lactose, and solids-not-fat. Egger’s test for publication biases was not significant for all responses of interest. In conclusion, the supplementation of Cr improves DMI and the improvement is greater for AFP than for BFP. Milk production is also improved by Cr-supplementation.